Edukasi dan Peningkatan Pengetahuan Ibu tentang Karies Gigi dalam Upaya Pemeliharaan Kesehatan Gigi dan Mulut Anak di Gampong Lam Ue Kabupaten Aceh Besar - Mufizarni; Reca; Elfi Zahara; Lina Farsia; Cut Fazlil Hanum; Cut Aja Nuraskin (Poltekkes Kemenkes Aceh, 2023)
Efforts to maintain dental and oral health should be carried out from an early age. Entering the age of 6-12 years, the risk of children experiencing caries is quite high, knowledge, attitudes and behavior of parents, especially mothers, are needed in maintaining children's dental and oral health. Based on an initial survey conducted on 20 children aged 6-12 years in Gampong Lam Ue, Aceh Besar District, it was found that 16 of the 20 children had dental caries, with an average def-t value of 2.7 (moderate category) and an average def-t value of 2.7 (moderate category). DMF-T average: 3.1 (medium category). The purpose of this activity is to increase mother's knowledge about dental caries in an effort to maintain children's dental and oral health in Gampong Lam Ue, Aceh Besar District. In this community service, education was carried out to increase mother's knowledge about children's dental and oral health by counseling using the Lecture, Questions and Answers, Demonstration, Discussion and Simulation methods. The results of community service that have been carried out show that there is an increase in mother's knowledge in maintaining oral and dental hygiene in children with an increase before the intervention (pre-test) in the poor category (70.0%) and after the intervention (post test) in the category good (93.3%). Mothers are expected to increase information and knowledge about dental caries and maintenance of children's dental health through counseling and other information media both on the internet and mass media, dental and oral health books or can consult directly with dentists/dental nurses about their children's dental and oral health.